KEPENTINGAN TIONGKOK TERHADAP AFRIKA MELALUI FORUM ON CHINA-AFRICA COOPERATION (FOCAC) - Fenny Crosby Sinaga; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research explain about interest Tiongkok to Africa through Forum On China-Africa Cooperation (FOCAC). Economic development in Tiongkok the rapid and the lack of energy sources as a supporting factor the reason why Tiongkok increasingly strengthen its relationship with African countries rich in natural resources especially oil the strengthening of International cooperation in the field of energy is also done by Tiongkok.Tiongkok believe that between Tiongkok and African countries have a common good, namely frienship, peace, cooperation and development. FOCAC is cooperation forum founded by Tiongkok and Africa which was hold from 10 to 12 October 2000 in Beijing Tiongkok. Tiongkok focus on Africa through the cooperation in economic terms beginning at the Meeting Of the High-Level Conference (KTT) Tiongkok Africa that produces FOCAC since the year 2000.In analyze the problem in this study, the authors use the theory of Graham T. Allison where it can be analyze that inthe manufacture of foreign policy of country in influenced by the element of domestic, wether it be values embraced by the leadership of the interest of the bureucrats until on the way leaders analize the domestic situation is very influential about removal decision.Keywords : Tiongkok, Africa, Economic Development, FOCAC (Forum On China-Afrika Cooperation), National Interest